Receptor Protein Tyrosine Phosphatase α–Mediated Enhancement of Rheumatoid Synovial Fibroblast Signaling and Promotion of Arthritis in Mice. Issue 2 (February 2016) - Stanford, Stephanie M.; Svensson, Mattias N. D.; Sacchetti, Cristiano; Pilo, Caila A.; Wu, Dennis J.; Kiosses, William B.; Hellvard, Annelie; Bergum, Brith; Muench, German R. Aleman; Elly, Christian; Liu, Yun‐Cai; den Hertog, Jeroen; et al.
Abstract : Objective: During rheumatoid arthritis (RA), fibroblast‐like synoviocytes (FLS) critically promote disease pathogenesis by aggressively invading the extracellular matrix of the joint. The focal adhesion kinase (FAK) signaling pathway is emerging as a contributor to the anomalous behavior of RA FLS. The receptor protein tyrosine phosphatase α (RPTPα), which is encoded by the PTPRA gene, is a key promoter of FAK signaling. The aim of this study was to investigate whether RPTPα mediates FLS aggressiveness and RA pathogenesis. Methods: Through RPTPα knockdown, we assessed FLS gene expression by quantitative polymerase chain reaction analysis and enzyme‐linked immunosorbent assay, invasion and migration by Transwell assays, survival by annexin V and propidium iodide staining, adhesion and spreading by immunofluorescence microscopy, and activation of signaling pathways by Western blotting of FLS lysates. Arthritis development was examined in RPTPα‐knockout (KO) mice using the K/BxN serum–transfer model. The contribution of radiosensitive and radioresistant cells to disease was evaluated by reciprocal bone marrow transplantation. Results: RPTPα was enriched in the RA synovial lining. RPTPα knockdown impaired RA FLS survival, spreading, migration, invasiveness, and responsiveness to platelet‐derived growth factor, tumor necrosis factor, and interleukin‐1 stimulation. These phenotypes correlated with increased phosphorylation of Src on inhibitory Y 527 and decreased phosphorylation of FAK on stimulatory Y 397 . Treatment of RA FLS with an inhibitor of FAK phenocopied the knockdown of RPTPα. RPTPα‐KO mice were protected from arthritis development, which was due to radioresistant cells. Conclusion: By regulating the phosphorylation of Src and FAK, RPTPα mediates proinflammatory and proinvasive signaling in RA FLS, correlating with the promotion of disease in an FLS‐dependent model of RA.